Hurricane Frequency and Intensity May Decrease Dispersal of Kemp’s Ridley Sea Turtle Hatchlings in the Gulf of Mexico - DuBois, Morgan J.; Putman, Nathan F.; Piacenza, Susan E. (Frontiers in Marine Science, 2020)
Environmental variability can be an important factor in the population dynamics of many species. In marine systems, for instance, whether environmental conditions facilitate or impede the movements of juvenile animals to nursery habitat can have a large influence on subsequent population abundance. Both subtle differences in the position of oceanographic features (such as meandering currents) and major disturbances (such as hurricanes) can greatly alter dispersal outcomes. Here, we use an ocean circulation model to explore seasonal and annual variation in the dispersal of post-hatchling Kemp’s ridley sea turtles (Lepidochelys kempii). We simulated the transport of 24 cohorts of young Kemp’s ridley dispersing from three main nesting areas in the western Gulf of Mexico to describe variability in transport during the main hatching season and across years. We examined whether differences in transport distance among Kemp’s ridley cohorts could be explained by hurricane events. We found that years with high numbers of hurricanes corresponded to shorter dispersal distances within the first six months. Our findings suggest that differences in dispersal among sites and the impact due to hurricanes could influence the survivorship and somatic growth rates of turtles from different nesting sites and hatching cohorts. Considering such factors in future population assessments may aid in predicting how the potential for increasing tropical storms, a phenomenon linked to climate change, could affect Kemp’s ridley and other populations of sea turtles in the Atlantic.